The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1097/01.asw.0000801524.42349.4d
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Healing Outcomes in Primary Care Patients with Diabetic Foot Ulcers: A Retrospective Study in a Multiethnic Sample

Abstract: OBJECTIVE:To identify and determine patient-and ulcer-related factors associated with healing outcomes within 3 months for patients with diabetic foot ulcer (DFU) in a multiethnic primary care sample. METHODS:Retrospective data were collected over 3 months from 520 primary care patients with a DFU between April 1, 2016 and March 31, 2017. Multivariable prevalence ratios (PRs) were calculated using Poisson regression to find associations between patient-and ulcer-related factors and healing outcomes. RESULTS:Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 42 publications
1
8
3
Order By: Relevance
“…The findings align with a recent study conducted in Singapore in a chronic wound population in primary care 21 . The mean wound area in the present study (7.8 ± 21.2 cm 2 ) was comparable to the findings of a recent study conducted in Singapore on patients with diabetic foot ulcer (7.0 ± 12.5 cm 2 ) 22 . However, the mean age of the participants (27.9 ± 12.4 years) in the present study was much younger compared with the reported age of the patients with chronic wounds (61.2 ± 4.6 years) and diabetic foot ulcers (66.3 ± 11.3 years) 21,22 …”
Section: Discussionsupporting
confidence: 89%
“…The findings align with a recent study conducted in Singapore in a chronic wound population in primary care 21 . The mean wound area in the present study (7.8 ± 21.2 cm 2 ) was comparable to the findings of a recent study conducted in Singapore on patients with diabetic foot ulcer (7.0 ± 12.5 cm 2 ) 22 . However, the mean age of the participants (27.9 ± 12.4 years) in the present study was much younger compared with the reported age of the patients with chronic wounds (61.2 ± 4.6 years) and diabetic foot ulcers (66.3 ± 11.3 years) 21,22 …”
Section: Discussionsupporting
confidence: 89%
“…Healing prediction is one of the most challenging issues in wound management and is a key component to achieve wound closure. 14 Most health conditions are complex, but none more so than chronic wounds. The multifactorial complex nature of wounds, in particular those that are chronic, makes prediction by humans difficult (ie, not an exact science).…”
mentioning
confidence: 99%
“…In this sense, moving research from isolated risk factors to "wound" pattern recognition, by means of identification of the complex pattern of interactions among the web of the wound and patient impactors, is necessary. 14,27,28 A sort of Wound Bed Preparation (WBP) on steroids! Although difficult, it is feasible to identify and even understand the regularities of a web of impactors using real data and statistical modelling.…”
mentioning
confidence: 99%
See 2 more Smart Citations